AS DINÂMICAS DA RELAÇÃO ENTRE COMÉRCIO E INDÚSTRIA EM FRANCA (SP) - De Azevedo Do Carmo, Judite; Ortigoza, Silvia Aparecida Guarnieri [UNESP] (Universidade Federal do Paraná, 2016)
The objective of this text is a reassessment of part of the results of a study developed by Carmo (2012), which considers the local productive arrangement (LPA) specialized in the production of men's footwear in Franca, São Paulo. The central idea of this article was to construct an analysis of the dynamics of the current relationship established between trade and industry, highlighting the theoretical questions inherent to the theme. Furthermore, the article explored the understanding that reflection is needed to unveil the articulations of the market in the production dynamics of LPA, given that the market plays a vital role via its strategies, which can trigger greater production demand. The proposed analysis permitted the clarification of the transformations that occurred in the production process during the final decades of the 20th century, which conditioned the tightening of relations between the industry and the market, as both activities are performed in mutual dependence; and in the LPA, highlighted here, the relationship between the industries and the local market should be expanded, given the observed existence of a monopoly on the marketing of shoes by the shoe industries through their own shops or franchises, having little relationship with third-party commercial establishments.
The dynamics of the relationship between trade and industry in Franca (SP)
Keywords: Local Productive Arrangement; New Marketing Strategies; Production; Specialized retail